The Communication Strategies of Public Relations in the Class I Immigration Office Special for Immigrations Checkpoins (TPI) Medan in Managing Public Complaint - Amirul Umam; Dewi Kurniawati; Hendra Harahap (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The title of this study is the communication strategies of public Relations in Class I Immigration Office Special for TPI Medan ini complaint management. The objectives of this study are first, to analyze the communication strategies of immigration information and communication division in complain managemenyt; third to analyze the effort expended in overcoming the challenges in the complaint management. The study carried out in TPI Medan Class I Immigration Office employs and interpretive descriptive qualitative method with three informants from Immigration Public Reltions and four additional triangulations informants. The findings show the communication strategies of Immigration Public Relations implement a complaint counter facility and social media to communicate with the public regarding complaint management. The obstacles in complaint management encountered by the Public Relations include a lack of coordinations among divisions and the public’s minimum knowledge about the immigrations rule. Therefore, Immigration Public Relations is trying to overcome the obstacles by holding monthly evaltuation meetings and disseminating immigration rules through infographics on social media.